BIOMEDICINES-CINA AGAINST COVID-19: CONTROLLED PLANT DISEASES ENRICHED SCIENCE AND TECHNOLOGY COMMUNICATION GREEN ECONOMY: Biomedicines-Cina against COVID-19: Controlled Plant Diseases - Datta, Subhas Chandra (International Journal of Research -GRANTHAALAYAH, 2020)
The economic-plant-mulberry is infected by different pathogens causing diseases and significantly reduces silk production. Though pesticides are the most effective means of control, but they are expensive and not environment friendly. On the other hand, the ongoing spread of the novel coronavirus, forming epidemic, affecting human civilizations, because recently, no appropriate antiviral drugs for effective treatments or vaccines against COVID-19. To meet the challenge, it is reported that the therapeutic value of traditional-, complementary- and alternative-biomedicines-Artemisia nilagirica, has been used for centuries, to overcome various medical disorders. So, to concur with the situation, it will require new and more efficient solutions, technologies, and products. Present pretreatment with ultra-high-diluted biomedicines-Cina, prepared from the flowering meristems of Artemisia nilagirica (Clarke) pamp, mixed with water at an extremely low dose, were applied by foliar spray once daily for 15 days @ 10 ml/plant, against naturally occurring, root-knot-, leaf spot-, powdery mildew-, mosaic- and tukra- mulberry diseases, in field trials and silkworms rearing. Pretreatment-investigations have revealed that ultra-high-diluted-Cina, highly effective in ameliorating different mulberry-diseases by inducing their natural defense-response against pathogens-infection and leaving no residual-toxicity in the leaves to affect the growth of silkworms also. It can be concluded that the ultra-high-diluted, eco-friendly easily-available, easily applicable-Cina, at an extremely low dose, not only used as a potential-biomedical-drug against various plant-diseases, by inducing natural-defense- response, but also, it may be effective against COVID-19 for vaccinations and clinical trials by boosting the natural immune system for the improvement of Science and Technology communication cost-effectiveness green-economy and biodiversity conservations as well as bio-applications issues. And the future clinical-scientists develop all aspects of clinical-case-reports by publishing in the appropriate medical research archives, with the sincere hope that this crisis will soon be over and the whole world, may fight against the COVID-19 war, retaining normal forms of human civilizations globally.